Ecological risks and opportunities from engineered artificial flooding as a means of achieving environmental flow objectives. Issue 7 (19th June 2014) - Bond, Nick; Costelloe, Justin; King, Alison; Warfe, Danielle; Reich, Paul; Balcombe, Stephen
Abstract : Restoration of floodplain ecosystems through the reinstatement of floods is often hampered by insufficient water as a result of competing human demands. An emerging alternative approach relies on floodplain infrastructure – such as levees, weirs, regulators, and pumps – to control water levels within floodplains without requiring landscape‐scale overbank floods. This technique, albeit water efficient and capable of achieving some ecological targets, does not mimic the hydraulics, hydrodynamics, and lateral connectivity of natural floods. Engineering approaches like this may risk detrimental ecological outcomes, including reductions in biotic connectivity, river–floodplain productivity, and water quality, and thus may fail to support the range of ecological processes required to sustain healthy river–floodplain systems. Here, we review the potential benefits, risks, and mitigation options associated with engineered artificial flooding. Given the growing challenge of equitable water allocation, further research on and monitoring of engineered floods as a tool to sustain floodplain ecosystems are urgently required.